2014
DOI: 10.1371/journal.pgen.1004285
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predisposition to In Situ and Invasive Lobular Carcinoma of the Breast

Abstract: Invasive lobular breast cancer (ILC) accounts for 10–15% of all invasive breast carcinomas. It is generally ER positive (ER+) and often associated with lobular carcinoma in situ (LCIS). Genome-wide association studies have identified more than 70 common polymorphisms that predispose to breast cancer, but these studies included predominantly ductal (IDC) carcinomas. To identify novel common polymorphisms that predispose to ILC and LCIS, we pooled data from 6,023 cases (5,622 ILC, 401 pure LCIS) and 34,271 contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 40 publications
(36 reference statements)
0
31
1
1
Order By: Relevance
“…Only one low-penetrance variant was specifically associated with ILC in a pooled, post hoc analysis of 36 case–control studies [106]. …”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…Only one low-penetrance variant was specifically associated with ILC in a pooled, post hoc analysis of 36 case–control studies [106]. …”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…The ability to characterize entire genomes at base pair level using massively parallel sequencing technologies provides a unique opportunity to unravel genotypic-phenotypic associations in breast cancer, which can be exploited for the identification of drivers of tumourigenesis [17]. Invasive lobular breast cancer (ILC) is accounts for 10% -15% of all invasive breast carcinomas and it has distinct etiological, clinical and biological characteristics compared with the more common invasive ductal type carcinoma (IDC) [18]. In Iran, breast cancer is ranked first among malignancies in women [19].…”
Section: Introductionmentioning
confidence: 99%
“…While there are genetic risk factors which are specific for either lobular or ductal BC, a limitation of our study was that the information on histological subtype of the tumors was relatively sparse and so the power to detect DCIS specific associations was limited.…”
Section: Discussionmentioning
confidence: 99%
“…Even though a growing number of common, low‐penetrance susceptibility loci for invasive BC are being identified, comparatively few attempts to detect single nucleotide polymorphisms (SNPs) that are specific for breast carcinoma in situ (BCIS) have been made so far and of these several were underpowered . A previous study conducted within the Million Women Study identified 2p‐rs4666451 as being more strongly associated with BCIS risk than with invasive disease .…”
mentioning
confidence: 99%